Iryna Ivakhnenko. Vasyl’ Danylevych pedagogical activites - Ivakhnenko, Iryna (Young Scholars Grinchenko – Seton International Journal, 2021)
Iryna Ivakhnenko. Vasyl’ Danylevych pedagogical activites Abstract. The article is devoted to Vasyl’ Danylevych, as well as known Ukrainian historian, scientist, public figure, Professor, archaeologist, numismatist, Museum critic and teacher. The relevance of the article consist in the study of the pedagogical activity of the Ukrainian historian at the end of the 19th – first third of the 20th century. The future teacher was born in the family of a hereditary nobleman, he was graduated from the 4th Kyiv gymnasium and the history and philology faculty of the St. Volodymyr University in Kyiv. Vasyl’ Danylevych’s mentor was Professor Volodymyr Antonovych, under whose guidance he wrote the competition work “An Outline of the History, the Polotsk Land until the end of the 14th century”. For this work he received a gold medal and the right to become a professorial scholarship holder and continue his studies in the master’s program. He became a member of Professor Antonovich’s Kyiv School of Historians. Vasyl’ Danylevych’s scientific and pedagogical work lasted almost 40 years and covered his work as a teacher of the Baku real School in 1896–1897, a teacher of the Yuryevsky (Tartu) real School in 1897–1900, Revelskaya Alexandrievskaya Gymnasium in 1901, a teacher at the Kharkiv Gymnasium in 1902–1907, and a privatdozent at Kharkiv University in 1903–1907 and the University of St. Volodymyr 1907–1915 in Kyiv and at the higher female courses in Kyiv, privatdozent of the University of Warsaw in 1915–1917, professor at the Ukrainian university in 1918–1920 in Kyiv and the Kyiv Institute of Public Education in 1920–1931, etc. During his seminal pedagogical life, the historian developed and conducted many lectures. Among them were courses on the history of ancient Russian (Ukrainian) lands, historical geography, source studies, the history of Russian colonization, etc. He turned his attentionto the history of the Ukrainian Cossacks, socio-economic and cultural development of Ukrainian lands, also covering issues of historical geography. V. Danylevych actively collaborated with his students, attracted them to various fields of activity. Speaking of Vasyl’ Danylevych as a teacher, his students recalled he took a very attentively and critical approach to his work. It was these qualities in his works allowed to prove himself and make a significant contribution not only to the field of pedagogical work, but also to his scientific activities in general. Returning to Ukraine in 1918, V. Danylevych expressed a desire to work for the benefit of the Ukrainian people and Ukrainian science. In 1918–1920, he worked as a professor at the Kyiv State Ukrainian University, which was founded by Hetman Pavlo Skoropadsky, and in 1920–1931, he taught at the Dragomanov Kyiv Higher Institute of Public Education. His lecture courses were devoted to ancient Russian (Ukrainian) history and historiography. In 1924, he became a member of the All-Ukrainian archaeological committee of the Higher School of Economics and a full member of the research department of the history of Ukraine M. Hrushevsky, headed the subsection of the history of material culture. The direction of V. Danylevych’s scientific work was Studios on the archeology of Ukraine and the history of governance in Sloboda Ukraine in the 17th – 18th centuries. Keywords: Vasyl` Danylevych, historian, professor, pedagogical activity, St. Volodymyr University, Professor Antonovych Kyiv School of Historians, Kharkiv University, the end of the 19th – the first third of the 20th century, St. Volodymyr University, Kyiv, University of Warsaw.